Mitochondrial Behavior in Axon Degeneration and Regeneration - Wang, Biyao; Huang, Minghao; Shang, Dehao; Yan, Xu; Zhao, Baohong; Zhang, Xinwen (Frontiers in Aging Neuroscience, 2021)
Mitochondria are organelles responsible for bioenergetic metabolism, calcium homeostasis, and signal transmission essential for neurons due to their high energy consumption. Accumulating evidence has demonstrated that mitochondria play a key role in axon degeneration and regeneration under physiological and pathological conditions. Mitochondrial dysfunction occurs at an early stage of axon degeneration and involves oxidative stress, energy deficiency, imbalance of mitochondrial dynamics, defects in mitochondrial transport, and mitophagy dysregulation. The restoration of these defective mitochondria by enhancing mitochondrial transport, clearance of reactive oxidative species (ROS), and improving bioenergetic can greatly contribute to axon regeneration. In this paper, we focus on the biological behavior of axonal mitochondria in aging, injury (e.g., traumatic brain and spinal cord injury), and neurodegenerative diseases (Alzheimer’s disease, Parkinson’s disease, Amyotrophic lateral sclerosis) and consider the role of mitochondria in axon regeneration. We also compare the behavior of mitochondria in different diseases and outline novel therapeutic strategies for addressing abnormal mitochondrial biological behavior to promote axonal regeneration in neurological diseases and injuries.